Dichloroacetate Prevents Cisplatin-Induced Nephrotoxicity without Compromising Cisplatin Anticancer Properties - Galgamuwa, Ramindhu (J Am Soc Nephrol, 2016)
Cisplatin is an effective anticancer drug; however, cisplatin use often leads to nephrotoxicity, which limits its clinical effectiveness. In this study, we determined the effect of dichloroacetate, a novel anticancer agent, in a mouse model of cisplatin-induced AKI. Pretreatment with dichloroacetate significantly attenuated the cisplatin-induced increase in BUN and serum creatinine levels, renal tubular apoptosis, and oxidative stress. Additionally, pretreatment with dichloroacetate accelerated tubular regeneration after cisplatin-induced renal damage. Whole transcriptome sequencing revealed that dichloroacetate prevented mitochondrial dysfunction and preserved the energy-generating capacity of the kidneys by preventing the cisplatin-induced downregulation of fatty acid and glucose oxidation, and of genes involved in the Krebs cycle and oxidative phosphorylation. Notably, dichloroacetate did not interfere with the anticancer activity of cisplatin in vivo. These data provide strong evidence that dichloroacetate preserves renal function when used in conjunction with cisplatin.